Δ18O, δ13C, trace elements and REE in situ measurements coupled with U–Pb ages to reconstruct the diagenesis of upper triassic atoll-type carbonates from the Panthalassa Ocean. (October 2020) - Peyrotty, G.; Brigaud, B.; Martini, R.
Abstract: Owing to their isolated oceanic setting, atoll-type carbonates are well suited for documenting carbonate deposition and diagenesis in oceanic environments away from continental influence. The atoll-type Dalnegorsk limestone (Taukha Terrane, Russian Far East), deposited in the gigantic but poorly-documented Panthalassa Ocean, preserves a complete record of the diagenetic evolution of an Upper Triassic system, out of the Tethyan domain. To study the diagenesis of this carbonate system, we developed a novel analytical workflow, combining cathodoluminescence petrography with high-resolution analyses of environmental proxies in calcitic cements (δ 18 O, δ 13 C, REEY, trace and minor/major elements) and in situ U–Pb dating of calcite cements to precisely reconstruct the chronology of the diagenetic events. We combined these lines of evidence to establish a model of atoll evolution, from deposition to dismantling, based on 10 identified diagenetic episodes. The Dalnegorsk limestone records emergence at the Norian-Rhaetian transition, marked by meteoric and evaporitic cements, followed by dismantling of the atoll edges after drawning in the Early Jurassic. Neomorphism of calcitic shells occurred at the onset of calcitic sea conditions during the Toarcian-Bajocian. The limestone was thoroughly cemented during the Middle/Late Jurassic, and accreted within the Taukha Terrane during the Late Jurassic/Early Cretaceous. Accretion resulted in fracturing, brecciation, and recrystallisation of the Dalnegorsk limestone. This model is potentially applicable to any similar atoll system, irrespective of age. The evidence presented here extends our knowledge of Late Triassic environments in the Panthalassa Ocean, and more generally, our understandingg of mid-oceanic limestone formation and evolution. Highlights: Diagenetic characterisation of Upper Triassic atoll-type limestone from Panthalassa. δ 18 O, δ 13 C, REE and trace elements in situ measurements on calcite cements. U–Pb dating of calcite cement to precisely constrain the timing of diagenetic events. Diagenetic evolution model of the studied atoll, from its deposit to its accretion.